Rituximab treatment in non-lupus full-house nephropathy: A case report - Caroline Gee; Dao Le; Matthew D. Nguyen; Anthony Sisk; Ramy Hanna (SAGE Open Medical Case Reports)
Non-lupus full-house nephropathy describes a pattern of “full-house” immunofluorescence on renal biopsy in the absence of clinical or serologic markers for systemic lupus erythematosus. It is a rare disease with a broad range of etiologies, including idiopathic, secondary, or a prodrome of systemic lupus erythematosus. Current treatment options are lacking, with mixed results in the literature for varied immunosuppressive regimens. Rituximab, a selective anti-CD20 B-cell monoclonal antibody, has shown success in immune-complex mediated glomerular diseases but has not been commonly used or studied in non-lupus full-house nephropathy. Here, we present a case of non-lupus full-house nephropathy that was refractory to first-line immunosuppressants, in which two rounds of rituximab treatment achieved a positive response. This case emphasizes the need for systemic analysis of rituximab use in non-lupus full-house nephropathy, particularly given its mixed etiologies and presentations.